(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2025)
The aim of the article is to identify and analyze the logistics planning process in a production and commercial enterprise in the SME sector. The article uses the literature analysis method and the case study method. The article attempts to characterize the process nature of logistics planning and the importance of logistics strategy in this process.